2018
DOI: 10.1016/s0140-6736(17)33104-5
|View full text |Cite
|
Sign up to set email alerts
|

Modern contraceptive use, unmet need, and demand satisfied among women of reproductive age who are married or in a union in the focus countries of the Family Planning 2020 initiative: a systematic analysis using the Family Planning Estimation Tool

Abstract: SummaryBackgroundThe London Summit on Family Planning in 2012 inspired the Family Planning 2020 (FP2020) initiative and the 120×20 goal of having an additional 120 million women and adolescent girls become users of modern contraceptives in 69 of the world's poorest countries by the year 2020. Working towards achieving 120 × 20 is crucial for ultimately achieving the Sustainable Development Goals of universal access and satisfying demand for reproductive health. Thus, a performance assessment is required to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
207
6
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(221 citation statements)
references
References 7 publications
2
207
6
6
Order By: Relevance
“…This dynamic differed in the control groups, as the prevalence in Burkina Faso did not change from month 6 to month 12, when it reached 29%, a proportion that did not overtake the 30% in national prevalence projected for 2018. 22 In DR Congo, however, the prevalence in the control group kept increasing until 12 months, when it reached 35% and surpassed by 8 percentage points the 27% in projected prevalence for 2017 for married women in Kinshasa. 23 It was unlikely that women from control study sites went to intervention sites to receive the package, or that components of the package reached contraceptive services in control sites, as neither situations were reported by service providers or research assistants assigned to each of the centres.…”
Section: Discussionmentioning
confidence: 93%
“…This dynamic differed in the control groups, as the prevalence in Burkina Faso did not change from month 6 to month 12, when it reached 29%, a proportion that did not overtake the 30% in national prevalence projected for 2018. 22 In DR Congo, however, the prevalence in the control group kept increasing until 12 months, when it reached 35% and surpassed by 8 percentage points the 27% in projected prevalence for 2017 for married women in Kinshasa. 23 It was unlikely that women from control study sites went to intervention sites to receive the package, or that components of the package reached contraceptive services in control sites, as neither situations were reported by service providers or research assistants assigned to each of the centres.…”
Section: Discussionmentioning
confidence: 93%
“…26 Even in high-resource countries, such as the United States of America, politicians have taken decisions that are likely to limit women's access to contraceptive agents by proposing the removal of the mandate for health insurance to cover contraception that will effectively make them more expensive for women. This will in part be due to access to and delivery of health care in countries with more limited financial resources but in addition, there are sociocultural barriers to accessing information, services and supplies of agents for contraception, many of which are also be important for managing HMB.…”
Section: Equity Of Access To Treatmentmentioning
confidence: 99%
“…This will in part be due to access to and delivery of health care in countries with more limited financial resources but in addition, there are sociocultural barriers to accessing information, services and supplies of agents for contraception, many of which are also be important for managing HMB. 26 Even in high-resource countries, such as the United States of America, politicians have taken decisions that are likely to limit women's access to contraceptive agents by proposing the removal of the mandate for health insurance to cover contraception that will effectively make them more expensive for women. 27 This may have an unintended impact on women's ability to afford contraceptive agents for treatment of HMB and introduce barriers to equity in health care.…”
Section: Equity Of Access To Treatmentmentioning
confidence: 99%
“…Other evidence shows that the unmet need for modern methods ranges from 10.2% to 39.9% in Nicaragua and the democratic republic of Congo, respectively. The modern contraceptive prevalence rate (mCPR) is as lowest (2.6%) in Somalia and as the highest (77.4%) in Nicaragua (5). According to the DHS report of Sub Sahara Africa countries indicated that mCPR among married women was 2.3% in Ethiopia (2005-2011), 2.4% in Malawi (2004)(2005)(2006)(2007)(2008)(2009)(2010), and a dramatic 6.9% in Rwanda (2005-2010), (6).…”
Section: Introductionmentioning
confidence: 99%